The Pathogenic Aspects of Human Parvovirus B19 NS1 Protein in Chronic and Inflammatory Diseases - Sedigheh Jalali; Ali Farhadi; Gholamreza Rafiei Dehbidi; Shirin Farjadian; Sedigheh Sharifzadeh; Reza Ranjbaran; Noorossadat Seyyedi; Sepide Namdari; Abbas Behzad-Behbahani (Interdisciplinary Perspectives on Infectious Diseases)
Background. The nonstructural protein (NS1) of human parvovirus B19 (hPVB19) is considered to be a double-edged sword in its pathogenesis. NS1 protein promotes cell death by apoptosis in erythroid-lineage cells and is also implicated in triggering and the progression of various inflammation and autoimmune disorders. Objectives. We investigated the possible role of hPVB19 NS1 in the modulation of proinflammatory cytokines in nonpermissive HEK-293T cells. Methods. A plasmid containing the fully sequenced NS1 gene (pCMV6-AC-GFP-NS1) was transfected into HEK-293T cells. Transfection efficiency was assessed by fluorescent microscopy over time. Mock (pCMV6-AC-GFP) transfected cells were used as controls. The percentage of apoptotic cells was measured by flow cytometry at 24, 48, and 72 h posttransfection. Interleukin 6 (IL-6) mRNA, as a pleiotropic cytokine, was measured by real-time PCR. Furthermore, cellular supernatants were collected to determine the type and quantity of cytokines produced by mock- and NS1-transfected cells using flow cytometry. Results. Fold change in the expression level of IL-6 mRNA in transfected cells after 72 hr of incubation was found to be 3.01 when compared with mock-transfected cells; however, cell apoptosis did not happen over time. Also, the concentration of cytokines such as IL-2, IL-6, IL-9, IL-17A, IL-21, IL-22, interferon (IFN)-γ, and tumor necrosis factor α (TNF-α) increased in NS1-transfected cells. Conclusions. Overall, our results indicated that proinflammatory cytokine levels had increased following the expression of hPVB19 NS1 in HEK-293T cells, consistent with a role for NS1 expression facilitating the upregulation of inflammatory reactions. Therefore, hPVB19 NS1 function may play a role in the progression of some chronic and inflammatory diseases.